2007
DOI: 10.1111/j.1751-553x.2007.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease: the Lebanese experience

Abstract: Summary Sickle cell disease (SCD), the commonest single gene disorder worldwide, is an inherited disease that has different clinical and hematological manifestations in different populations. The objective of this study is to describe the characteristics of the Lebanese SCD population. This was a retrospective study that included information on 387 patients with either sickle cell anemia (SS) or sickle beta‐thalassemia (ST). The mean (±SD) age was 17.9 years (±12.5), and the mean (±SD) follow‐up was 9.3 ± 6.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…These estimates may be lower than the actual incidence because of the early discharge of newborns and lack of newborn screening at many institutions. Compared with international data, the carrier rate of sickle cell and other hemoglobin variants in Lebanon is similar to Brazil (approximately 2%) but almost twice that of Italy (1.2%) and lower than Saudi Arabia (1.3% to 21.3%) and Bahrain (11.2% to 16.4%; Haber et al, 2010;Inati et al, 2007;Jastaniah, 2011;Makhoul et al, 2005).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…These estimates may be lower than the actual incidence because of the early discharge of newborns and lack of newborn screening at many institutions. Compared with international data, the carrier rate of sickle cell and other hemoglobin variants in Lebanon is similar to Brazil (approximately 2%) but almost twice that of Italy (1.2%) and lower than Saudi Arabia (1.3% to 21.3%) and Bahrain (11.2% to 16.4%; Haber et al, 2010;Inati et al, 2007;Jastaniah, 2011;Makhoul et al, 2005).…”
mentioning
confidence: 65%
“…CCCL is affiliated with St. Jude's Children's Research Hospital in Memphis, Tennessee, and works in coordination with the AUBMC. The exact number of children affected with SCD in Lebanon is unknown but is estimated to be around 1,000, with the majority being Muslim and residing in the northern and southern regions of the country (Inati et al, 2007). The comprehensive sickle cell program at AUBMC provides state-of-the-art care to patients with this genetic disorder.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease was shown to be clustered in two geographic areas in North and South Lebanon and nearly all patients were Muslims74. The disease was severe and the major haplotype was the Benin haplotype.…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 98%
“…Hb S was present in 20.0% of the 55 couples included in this study, and it was the only abnormal Hb found. This high frequency is often reported in many parts of Africa, India, the Middle East, the Mediterranean area, and parts of Turkey (3,(34)(35)(36). In this study, all couples who were diagnosed as carriers of the Hb S mutation originated from the Syrian coast or the southern regions of Syria.…”
Section: Discussionmentioning
confidence: 95%